Specifics of defense and coping behavior among teachers experiencing a professional identity crisis - O. Sadovnikova, Nadezhda; B. Sergeeva, Tamara; S. Kotova, Svetlana; I. Khasanova, Irina; A. Domoratskaya, Valeriya (International Journal of Engineering and Technology, 2018)
The issues addressed in the article are of particular relevance due to the necessity to provide research background for creating the system of psychological and pedagogical support for the professional development of teachers in the conditions of permanent changes in the system of education. The aim of the article is to describe specific interrelations between the reflection and the parameters of the teacher's axiological sphere (in particular, life-purpose orientations). The following research methods were used: theoretical analysis of psychological and educational literature, phenomenological method, questionnaires, and methods of mathematical and statistical data processing (descriptive statistics, comparative analysis (the Mann-Whitney U test). The results of the theoretical and empirical research provide adequate grounds for the conclusion that there is a definite interrelation between the parameters of reflection and the parameters of life-purpose orientations. It is proved that in the conditions of a professional identity crisis the teachers experience a significant reduction in the levels of life-purpose orientations, which in turn leads to intensification of reflection processes. At the same time, the obtained results suggest that the teachers can successfully overcome their professional crisis in case of formation of the cognitive component of the biographical reflection, aimed at the analysis of actions and means of understanding and organizing their life events. Implications of the research results. The research results expand our understanding of the essence and emotional experience of the professional identity crisis. They can be used in the designing the process of psychological support for the activities and professional development of teachers.Â